A Comparative Study of The Leadership of Regional Heads, Political Cadres, and Civil Servants on Development Outcomes: The Perspective of Local Government Employees in Cirebon City - Amellia Amellia; Siti Khumayah (Siber Nusantara of Law and Politic Review, 2026)
The paper aims to look at the difference between the leadership styles of the regional heads who are political appointees and those who are civil servants (ASN) and some of them under President Jokowi are ousted by Acting Mayors or Regents who are administrative tools of the President. This paper is based on a comparative study in the city of Cirebon, which had a change of leadership to an ASN acting mayor. This research fills a research gap that prevails since most researches have focused much on performance in policy or innovations in delivering public services but not the leadership process. The other gap is that there is no direct comparison of the political cadres and the civil servant local heads in the same region. The research design is descriptive qualitative, comparative methodology which entails in depth interviews and field observation. The results indicate that the political cadres leadership is more susceptible to the political factor and more inclined toward the populist politics, and the civil servant leadership is more bureaucratic with its focus on professionalism, responsibility and sustainability of the public services. This research paper illuminates on the issue of political and administrative legitimacy and its influence on the style of leadership and its impact on the delivery of the services by the government.